Reviewed Study on the Performance & Optimization of Power Transformer Using Artificial Intelligence Technique: Exploring the Potential of Artificial Intelligence Techniques for Transformer Design Optimization (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Transformers are the core of electrical transmission and conveyance frameworks. The point of transformer design is to acquire the components of all pieces of the transformer so as to gracefully these information to the producer. The transformer ought to be designed in a way with the end goal that it is monetarily suitable, has low weight, little size, great performance and simultaneously it ought to fulfill all the requirements forced by worldwide principles. Numerous scientists have utilized Artificial Intelligence (AI) procedures for transformer design optimization (TDO) and performance investigation. Notwithstanding, the genuine capability of AI methods is yet to be completely investigated for TDO issues. This paper leads a concise survey of innovative work in the field of transformers utilizing ordinary optimization strategies, man-made brainpower based optimization procedures and recommends a portion of the new bio-propelled AI methods that can be utilized for TDO issues